PENGARUH UTILITARIAN DAN HEDONIC VALUE TERHADAP LOYALITAS PELANGGAN ONLINE DENGAN KEPUASAN PELANGGAN SEBAGAI MEDIASI - Jimmy Chandra; Rodhiah Rodhiah (STIE Trisna Negara OKU Timur, 2023)
The development of internet services is very rapid and has an impact on human daily life; now, various online transportation and ordering services have emerged, making human activities easier both for mobilization and for meeting other daily needs; one of the service providers is Company “X”. Loyalty is an important feature in business; having loyal consumers indicates potential repeat purchases of Company “X”. The goal of this study is to look at the impact of utilitarian and hedonic value factors on Company “X” customer loyalty in Jakarta, using customer happiness as a moderator. This study's demographic consists of Company “X” users in Jakarta. The sample size was 150 people who completed a questionnaire using SmartPLS 4. The results showed that utilitarian value had no effect on customer loyalty but had a positive and significant effect on customer satisfaction. Hedonic value has a positive and significant influence on customer satisfaction and customer loyalty. Customer satisfaction has a significant effect on customer loyalty. Utilitarian and hedonic values have a positive and significant impact on customer loyalty through customer satisfaction.performance. Keywords : Utilitarian Value, Hedonic Value, Customer Satisfaction, Customer Loyalty